Die hermeneutiese proses onderliggend aan Paulus se eksegese van Eksodus 17:6 en Numeri 20:7–11 in 1 Korintiërs 10:1–4 - Koning, Jacobus D. W. de (HTS teologiese studies, 2021)
The hermeneutical process underlying Paul’s exegesis of Exodus 17:6 and Numbers 20:7–11 in 1 Corinthians 10:1–4. In this article, Paul’s use of the Old Testament in 1 Corinthians 10:1–4 comes under scrutiny. In contrast with the theory of some modern scholars that Paul uses, ‘fanciful analogies’, ‘startling figurative claims’ and metaphors that ‘should not he pressed’, in reaching his conclusion that ‘the rock was Christ’, in 1 Corinthians 10:4c, it is indicated that Paul is indeed taking the original text, the Old Testament’s interpretation of the text, and the Jewish tradition of the interpretation of the text, seriously, in the light of the Christ-event. To prove this claim, research of the text (Exodus 17:6 & Numbers 20:7–11), that Paul uses in 1 Corinthians 10:1–4, is followed by research of the ‘world in front of that text’ (Deuteronomy 32, the Psalms and Second Temple Judaism).Contribution: The conclusion that is reached indicates that Paul established within the context of contemporary Jewish practices, a true dialogical relationship between an intertextual handling of the text, and his interpretation thereof in the light of the relevance of the Christ-event for the conflict in the Church of Corinth.